Lipid Changes After Switch From TDF to TAF in the OPERA Cohort: LDL Cholesterol and Triglycerides. (8th December 2021) - Mallon, Patrick W G; Brunet, Laurence; Fusco, Jennifer S; Prajapati, Girish; Beyer, Andrew; Fusco, Gregory P; Wohlfeiler, Michael B
Abstract: Background: Increases in lipids have been observed in people with HIV (PWH) switching from tenofovir disoproxil fumarate (TDF) to tenofovir alafenamide (TAF). We assessed changes in low-density lipoprotein cholesterol (LDL-C) and triglycerides (TG) following a switch from TDF to TAF. Methods: Adults with ≥1 lipid measure before and after switch from TDF to TAF were identified in the OPERA cohort. Multivariable linear regression using generalized estimating equations was used to estimate predicted changes in lipids over time on TAF, modeled flexibly with linear splines. Results: A total of 6451 PWH switched from TDF to TAF, of whom 4328 maintained all other agents. LDL-C increased significantly by 1.40 mg/dL/mo over the first 3 months on TAF, by 0.33 mg/dL/mo between 3 and 9 months and then plateauing beyond 9 months. TG increased significantly by 3.52 mg/dL/mo over the first 3 months of TAF, by 0.91 mg/mL/mo between 3 and 9 months and by 0.72 mg/mL/mo between 9 and 16 months, but decreased thereafter. Similar patterns were observed in analyses restricted to PWH who switched from TDF to TAF but maintained all other agents. Conclusions: TDF-to-TAF switch was associated with LDL-C and TG increases over the first 9 to 16 months on TAF. The dynamic patterns observed cannot be attributed to changes in other agents.